13 metastable states arising from a simple multifunctional unimolecular system. (February 2017) - Sanguinet, Lionel; Berthet, Jérôme; Szalóki, György; Alévêque, Olivier; Pozzo, Jean-Luc; Delbaere, Stéphanie
Abstract: A diarylethene core decorated with two benzooxazolidine side-arms through ethylenic spacers represents a smart example of multi-addressable system whose reversible responses could be selectively activated on demand. UV–Visible and NMR spectroscopies and electrochemical studies allow to overview its performances when stimulated by light, acid/base and electrons, then underlining its photochromic, acidochromic and electrochromic properties. The multichromophoric combination could be considered as multifunctional and multistate systems, as interconversions can be performed by different stimuli whereas each stimulus provides a specific metastable state. Graphical abstract: Highlights: A diarylethene joined to two benzooxazolidine by ethylenic spacers was synthesized. Photochromic, acidochromic and electrochromic responses were evidenced. The system is multistate (among the 18 possible states, 13 were underlined). The system is multifunctional (same interconversion performed by different stimuli).